Ustawowe determinanty działalności gospodarczej w świetle orzecznictwa sądów administracyjnych - Grzymisławska-Cybulska, Maria (Wydawnictwo Naukowe UAM, 2014)
The defi nition of “economic activity” formulated pursuant to the provisions of the Act on freedom of economic activity has been a subject of research and deliberations presented in literature. Thus it seems justifi ed to analyse the same against relevant judicial decisions. In this paper rulings of the Supreme Administrative Court and region al administrative courts given after 1 January 2004 have been analysed. In some cases, it was deemed reasonable to include opinions delivered by the Supreme Administrative Court in Warszawa and its branches before the reform of administrative judiciary. The basic deliberations are focused on the practical understanding of individual determinants of economic activity. The research was conducted with a view of establishing whether the understanding of particular characteristics of actual economic activity is clear, or whether their interpretation has posed or poses certain diffi culties or doubts. The existence of some common features has justifi ed the references to judicial decisions that were made pursuant to two statutory acts currently no longer binding, i.e. the Act of 23 December 1988 on economic activity and the Act of 19 November 1999: Law on economic activity. Hence, the inclusion in the analysis of judgments delivered by administrative courts in cases that had actually occurred prior to the entry into force of the currently binding Act on freedom of economic activity. Further, an account has been made for the fact that there are several defi - nitions of economic activity. Consequently, possible interpretations of the term that may emerge either in the scope of the statutory act itself, or in other branches of law where the same term ‘economic activity’ is used, have been analysed. The main goal of the research was to determine the manner in which current practice verifi es earlier views and to establish whether it is at all justifi ed to refer to the judgments delivered on the basis of previously applicable legal acts. Questions may also be asked about a possible change in the practical approach to defi ning and assessing individual features of economic activity.
Statutory determinants of economic activity in light of administrative courts decisions
Keywords: characteristics of economic activity; legal defi nition; judicature; administrative courts